Factors associated with the early termination of exclusive breastfeeding among mother-infant dyads in Samara-Logia, Northeastern Ethiopia - Amanuel Molla Beyene; Misgan Legesse Liben; Amit Arora (BMC, 2019)
Abstract Background The World Health Organization recommends that mothers should exclusively breastfeed their infants until 6 months of age due to the benefits for the mother and the child. There is documented evidence on exclusive breastfeeding from Ethiopia, but not specifically from Samara-Logia city administration. This study aimed to assess the factors associated with early termination of exclusive breastfeeding among mother-infant dyads in Samara-Logia, Ethiopia. Methods A cross-sectional study was conducted in March 2018. Data were collected on 484 randomly selected mother-infant dyads. The Kaplan Meier curve with the log-rank test was used to compare the survival difference. Cox regression models were used to identify the predictors of early termination of exclusive breastfeeding. Results The cumulative proportion of survival probability of exclusive breastfeeding to 6 months was 64.5%, with the median duration of 6 months. Mothers having partners with formal education [Adjusted hazard ratio (AHR): 0.58; 95% confidence interval (CI): 0.39, 0.85], receiving counseling on exclusive breastfeeding at antenatal check-up [AHR: 0.62; 95% CI: 0.43, 0.91], giving birth in a health institution [AHR: 0.50; 95% CI: 0.28, 0.88], initiating breastfeeding within the first hour [AHR: 0.41; 95% CI: 0.24, 0.68], and perceiving breast milk adequate for the first 6 months [AHR: 0.17; 95% CI: 0.12, 0.25] were associated with lower hazard of discontinuing exclusive breastfeeding before 6 months. Conclusion This study showed that the cumulative proportion of survival probability on exclusive breastfeeding was low in Samara-Logia city administration. Educating husbands to support their partners, strengthening infant feeding counseling, promoting institutional delivery, educating women about the benefit of early initiation of breastfeeding, and expanding urban health extension program are important to improve the duration of exclusive breastfeeding in Ethiopia.